Ethanol Extract of Areca Nuts was Able to Improve the Histopathological Features of P. Berghei-Induced Liver Damage in Mice - Alissa Anna Safira; Ika Fidianingsih; Dwi Nur Ahsani (Berkala Kedokteran, 2021)
Abstract: Adequate therapy is necessary to prevent further damage to the liver infected with Plasmodium sp. Areca catechu and curcumin have the potential for malaria therapy, and scientific evidence is required to examine such potential either alone or in combination. This experimental study used a posttest-only group design involving 24 male Swiss mice (Mus musculus) as the subjects divided into 6 groups (@4 mice). P. berghei was injected intraperitoneally in 5 groups, and different types of treatment (4 days, feeding tube) were administered to 4 groups (K1 = chloroquine, K3 = ethanol extract of Areca nuts + curcumin, K4 = ethanol extract of Areca nuts, K5 = curcumin). The doses were 0.012mg/kgBW of chloroquine, 150mg/kgBW of Areca nut ethanol extract, and 30mg/kgBW of curcumin. K2 was the unhealthy group (infected with P. berghei without therapy), while K6 was the normal/healthy group. Parasitemia was examined in 3 days after induction by P. berghei (inclusion criterion: parasitemia >5%, exclusion criterion: parasitemia >15%). The liver was embedded in paraffin blocks and stained with HE. Observations were made to identify the presence of necrosis, portal inflammation, and hemosiderin. The data of histopathological changes in the liver was expressed in percentages. The administration of Areca nut ethanol extract was able to provide better histopathological features than curcumin therapy alone, in combination, or chloroquine therapy (K4, no necrosis; mild portal inflammation = 50%, moderate = 25%; hemosiderin = 25%). Areca nut ethanol extract had yet to show histopathological features that resembled a healthy condition (K6 = normal inflammation, mild, moderate = 50%, 50%, 0%, respectively; hemosiderin = 0%). The ethanol extract of Areca nuts alone was shortly able to improve the histopathological features of P. berghei-induced liver damage in mice. Keywords: Areca nuts, Plasmodium berghei, histopathology of liver